(untitled) - Gerritsen, Tess (New York, 2017)
"The crime scene is unlike any that Detective Rizzoli and medical examiner Maura Isles have ever before encountered. The woman lies in apparently peaceful repose on her bed, and Maura finds no apparent cause of death, but there is no doubt the woman is indeed dead. The victim's eyes have been removed and placed in the palm of her hand, a gesture that echoes the terrifying films she produces. Is a crazed movie fan reenacting scenes from those disturbing films? When another victim is found, again with no apparent cause of death, again with a grotesquely staged crime scene, Jane and Maura realize the killer has widened his circle of targets. He's chosen one particular woman for his next victim, and she knows he's coming for her next. She's the only one who can help Jane and Maura catch the killer. But she knows a secret. And it's a secret she'll never tell"--
Kirkus Reviews
Publishers Weekly
Library Journal
Booklist
Adult
Keywords: Fiction; Rizzoli, Jane, Detective (Fictitious character); Fiction; Isles, Maura (Fictitious character); Fiction; Policewomen; Fiction; Women forensic scientists; Murder; Fiction; Investigation; Suspense fiction; Mystery fiction